1968
DOI: 10.1021/ja01011a059
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of velbanamine

Abstract: The oncolytic agents vinblastine and vincristine1-2 are "dimeric" alkaloids containing a pentacyclic indoline and a tetracyclic indole moiety. Fragmentation into these structural units is brought about readily by reduction in acidic media which in the case of vinblastine gives desacetylvindoline3 and velbanamine (14).4 These fragments are obvious intermediates in a synthesis of vinblastine, and we now describe the first total synthesis5 of velbanamine ( 14).Oxygenation6 of the isoquinuclidine V in Z-butyl alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The approach by Büchi relied on retroaldol cleavage of the β-hydroxyketone 644 to reveal the bridged lactam 645 embedded in a [6.3.1] ring system (Scheme 182a). 180,181 This intermediate was converted into velbamine in five more steps. In contrast, Narisada showed that the analogous bridged lactam 650 could be obtained via fragmentation of 649 under oxidative conditions using Pb(OAc) 4 in comparable yield (Scheme 182b).…”
Section: Application Of Bridged Lactams In Total Synthesismentioning
confidence: 99%
“…The approach by Büchi relied on retroaldol cleavage of the β-hydroxyketone 644 to reveal the bridged lactam 645 embedded in a [6.3.1] ring system (Scheme 182a). 180,181 This intermediate was converted into velbamine in five more steps. In contrast, Narisada showed that the analogous bridged lactam 650 could be obtained via fragmentation of 649 under oxidative conditions using Pb(OAc) 4 in comparable yield (Scheme 182b).…”
Section: Application Of Bridged Lactams In Total Synthesismentioning
confidence: 99%
“…respectively, less potent than alprazolam (8) in the same two assays. Somewhat less marked potency differences were noted for the 4-hydroxytriazole derivatives 9a-lla vs. 9 11.…”
Section: Resultsmentioning
confidence: 73%
“…1-Demethylation and 3-hydroxylation of diazepam produce several metabolites which retain much of the parent compound's activity. Temazepam (3), demethyldiazepam (2), and oxazepam (4) are quite active and unquestionably contribute to diazepam's biologic effect.la,b Triazolobenzodiazepines such as triazolam (7) and probably alprazolam (8) are primarily metabolized by «or 4-hydroxylation or both.19'20 «-Hydroxylation of these triazolo compounds reduces activity slightly (7 vs. 10 and 8 vs. 11). However, hydroxylation of triazoloand imidazobenzodiazepines at position 4 reduces potency considerably (see Results and Table II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first racemic synthesis of velbanamine ( 2 ) was disclosed by Büchi and co-workers in 1968, four racemic syntheses and two enantioselective syntheses have been reported in spite of several synthetic efforts toward the core structure [1724]. The practical synthesis of velbanamine ( 2 ) and a general approach toward structurally related alkaloids remain an intriguing task in the synthetic community.…”
Section: Introductionmentioning
confidence: 99%